Research and methodology in healthcare interpreting - Pöchhacker, Franz (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This paper reviews the evolution and main strands of research on interpreting in health care, one of the most important domains of inter - preting in the community. The diverse body of literature generated since about the 1970s is first described with regard to different disciplinary perspectives and then surveyed in terms of thematic orientations, including a focus on the interpreting product, interpreter performance, communicative practices, and the provision of care. A number of examples are cited to illustrate both the breadth of content and the variety of methods used. The latter are then discussed from an overall perspective with regard to some broad methodological distinctions and choices.